The Double Bind: Performing Arts in Hongkong - Lilley, Rozanna (The Australian journal of anthropology, 1991)
In Hongkong, local identity is muted not only by the master narrative of ‘history of Europe’, but by that of ‘Chinese history’ and ‘Chinese civilization’. This comprises a ‘double bind’ on those who write and present drama, and the dance. This paper examines the way in which the two master narratives both conflict and assist one another in the elite performing arts. It points a schematic model which tries to take account of the self-conscious efforts of some local intelligentsia to insert a specifically Hongkong dimension between the two master narratives. This cultural refiguration has much to do with the sense of instability and concern for the future which has recently gripped the island.